Lectin Histochemical Study of GalNac and GlcNac Containing Glycoconjugates in Colon Adenocarcinoma - Mohamad Reza Arab; Ali Reza Rojhan; Mehdi Jahantigh; Mehdi Mohammadi (Negah Institute for Scientific Communication, 2013)
Introduction: Alteration of terminal sugars of Glycoconjugates is one of the important aspects of neoplasia. The aim of the present study was to identify GalNac and GlcNac containing glycoconjugates in different grades of neoplastic cells in adenocarcinoma of colon.  Methods: Histological sections prepared from paraffin blocks belong to 30 patient of colon adenocarcinoma obtained from Khatam-Al-Anbia hospital in Zahedan, Iran and stained by H-E, PAS, WGA and SBA/Alcian blue lectins. Histologic slides were graded histochemically (0-3) according to staining intensity, and collected data were analyzed by SPSS software.  Results: Statistical analysis showed only a significant difference in staining intensity for SBA lectin P<0.001) . Furthermore with increasing the histopathological grades, the frequency of positivity of neoplastic cells for GalNac and GluNac was also increased.  Conclusion: The pattern of staining of neoplastic cells to WGA and SBA lectins were changed with increasing of histopathological grades.